MEMBANGUN KEDEWASAAN BERPOLITIK WARGA MASYARAKAT AKADEMIS MELALUI PENDIDIKAN KEWARGANEGARAAN - Widodo, Bali (JPK (Jurnal Pancasila dan Kewarganegaraan), 2018)
The maturity of university students and academic people in Bandung is still not good enough. There are some university students who can't accept the political difference or deliver their political aspirations well. They sometimes deliver their political intentions by doing anarchics actions. This way will lead to the danger of our country's unity since university student is the part of our country's future. Referring to this case, it is necessary to create the university students into the persons that have adequate political maturity. The material of democracy education in citizenship education is the solutive way to ask the university students to do polite political actions. The implementation the democracy values can help the students to have political maturity.